PENINGKATAN DAYA SAING KOPI RAKYAT DI KABUPATEN JEMBER - Prayuginingsih, Henik; Santosa, Teguh Hari; Hazmi, Muhammad; Rizal, Nanang Saiful (Jurnal Sosial Ekonomi Pertanian, 2012)
Jember has 16.882 ha of coffee plantation, which Â 5.601,31 ha of them are smallholder coffee. Smallholder coffee is often identified has Â low productivity and quality. This research wanted to know: (1)the advantage of smallholder coffee at District of Jember; (2) how to increase the advantage. Research was done on May â August 2012 (harvest periode) at Sub District of Silo, Sumberjambe, Ledokombo and Panti with 98 respondens which were choosen by Â stratified random sampling methode.Â The advantage was measured by Â DRCR dan PCR, in order to increase the advantage using the result of Cobb-Douglas model of multiple regression analize on production function.Â TheÂ result showÂ that: Â (1) there are two methode of post-harvest processing of coffee, they are wet process and dry process methode;(2) smallholder coffee at Jember has competitif and comparative advantage (PCR wet process methode is 0,3679 and dry process methode is 0,4261). (3) Balance fertilizing could increase Â the advantage, but just comparative advantage (DRCR decrease to Â 0,4907 on wet process methode and 0,3566 on dry process methode), on the other side competitive advantage was a little decrease (PCR wet process methode is 0,5056Â and Â 0,5089 on dry process methode).Â Further more, balance fertilizing could increase the profit from IDR 17.804.906/ha/year to Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â IDR 21.103.109/ha/year on wet process methode and from IDR 8.965.371/ha/year to Â Â Â Â Â Â Â Â Â Â Â IDR 17.112.813/ha/year on dry process methode. Key words: competitive advantage, comparative advantage, balance fertilizing